The Effect of Competence, Motivation, Physical Work Environment on the Performance of Depok City Regional Secretariat Employees - Trianita, Della Septia; Krisnandi, Herry; Digdowiseiso, Kumba (International Journal of Social Service and Research, 2024)
This study was to determine the effect of Competence, Motivation, and Physical Work Environment on the Performance of Employees at the Depok City Regional Secretariat. The research data is data that uses primary data. This data collection was in the form of a questionnaire to 119 respondents from the Regional Secretariat of the City of Depok. Data analysis techniques used descriptive analysis and inferential analysis with multiple linear regression and using the Statistical Product and Service Solution (SPSS) version 23.0 program. The results of multiple linear regression analysis show that the variables Competency (X1), Motivation (X2), and Physical Work Environment (X3) have a positive and significant effect on Employee Performance. The results of this study hope that agencies can improve Competence, Motivation, and Physical Work Environment which can support Employee Performance.